Ecohydrology of groundwater‐dependent grasslands of the semi‐arid Horqin sandy land of inner Mongolia focusing on evapotranspiration partition. Issue 6 (27th November 2015) - Wu, Yao; Liu, Tingxi; Paredes, Paula; Duan, Limin; Wang, Haiyan; Wang, Tianshuai; Pereira, Luis S.
Abstract: The Horqin sandy steppe is an ecosystem where groundwater‐dependent grasslands are main components. To study the dynamics of soil water and evapotranspiration, and its partition into transpiration and soil evaporation, the SIMDualKc model was applied to two sites in the Agula eco‐hydrological study area, Inner Mongolia, China. This model adopts the dual crop coefficient approach to compute daily crop evapotranspiration (ETc ) and uses a parametric function to compute capillary rise from a shallow watertable. The application refers to three years of field observations, 2008 with high rainfall and higher watertable, 2009 with low rainfall and lower watertable, and 2011 with average rainfall and watertable conditions. Model calibration and validation were performed comparing simulated against observed soil water content throughout the vegetation seasons, with regression coefficients close to 1.0 and small root mean square errors (RMSE < 0.013 cm 3  cm −3 ). The groundwater contribution represented 41–47% of the actual ETc in the higher rainfall year and 56–59% in the dry year, which clearly shows the role of groundwater in sustaining grasslands in the Horqin steppe. The ratio between transpiration and actual ETc ranged 88 to 94%, which is much higher than observations in other grasslands because capillary rise contributes to extraction by crop roots, not to soil evaporation. Simulations relative to lowering the watertable show that groundwater contribution decreases up to 25% for a dry year with a consequent decrease of transpiration of 24%. Hence, there is the need for developing appropriate groundwater protection measures to preserve the Horqin landscape. Copyright © 2015 John Wiley & Sons, Ltd.